THE ANALYSIS OF THE FORM OF GELUNG TEMPLE AT PEMAKSAN PANTI BATUR SARI TEMPLE IN WERDHI AGUNG VILLAGE BOLAANG MONGONDOW DISTRICT - I Komang Riski Jaya; Meyer Worang Matey; Ferdinand Pangkey (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2023)
This research was conducted in Werdhi Agung Village, Bolaang Mongondow Regency, North Sulawesi, which is the location of the Pemaksan Panti Batur Sari Temple. This research aims to reveal and describe the form, function and meaning contained in the Gelung Temple of Pura Panti Batur Sari from a religious and aesthetic perspective from a Hindu religious perspective. This research uses a qualitative approach to obtain actual information to answer existing problems. The data sources obtained in this research were obtained from observation, interviews with sources, and literature study. From the research results, it is known that the Gelung Temple at Pemaksan Panti Batur Sari Temple has a tall shape and a roof that tapers upwards as a symbol of a mountain. The temple is divided into three parts, namely the foot of the temple, the body of the temple, and the roof of the temple. Organic ornaments were also found, namely Flora, Fauna, Humans. Most of the ornaments in Gelung Temple are also realized in the form of Lelengisan ornaments.